Predicting Potential Bankruptcy PT. Wismilak Inti Makmur, Tbk Using The Altman Z-Score Method - Maulana, Wahyu; Andrianingsih, Very (Institut Agama Islam Negeri (IAIN) Madura, 2023)
Indonesia is one of the countries that are still pro and contra towards cigarettes. Cigarettes are considered one of the dangerous products for public health and safety, but on the other hand the cigarette industry is the largest contributor to tax revenue in Indonesia. This study aims to determine the company's financial performance and to determine the potential for bankruptcy using the Altman z-score method at PT. Wismilak Inti Makmur Tbk. The type of research is descriptive quantitative while the population is all financial reports published by companies and the sample is financial statements for 2017-2021. Data collection techniques using the method of documentation. The data analysis technique used the modified Altman z-score method. Based on the results of the analysis and discussion of the modified altman z-score, it can be concluded that the company's financial condition for the 2017-2021 period is in good or healthy condition because the Z-score value is > 2.6. Even though in 2021 the z-score will decrease slightly, it is not at risk of going bankrupt. Suggestions for companies, in order to maintain financial performance every year in order to stay in good health